Race, Gender, and Empire: The Strange Career of Women’s Voting Rights in Wyoming - Virginia Scharff (Transatlantica)
Historians have long puzzled over the fact that the earliest victories for women’s voting rights in the United States were won in the American West, far from the most prominent centers of women’s political activism. This essay argues that women won the vote in Wyoming Territory in 1869 due to a convergence of the post-Civil War politics of Reconstruction and the dynamics of white supremacist settler colonialism. White women’s rights emerged as a tool to expand the American empire in a place then mostly in the hands of Indigenous inhabitants.